Barriers to Undergraduate Students’ Participation in Solid Waste Management: A Case Study of the University of Nigeria, Nsukka - A.N, Odo; E.O, Okwor; J.I, Ofuebe (Journal of Home Economics Research, 2024)
The study focused on proper solid waste management practices among the undergraduates of the University of Nigeria, Nsukka. Specifically, it determined barriers to undergraduate students’ participation in solid waste management and ways of enhancing such participation. It was a survey. The population was made up of undergraduates. Questionnaire was used for data collection. Frequencies, percentages and Chi-square (χ²) were used for data analysis. Findings include 13 barriers to undergraduates’ proper solid waste management practices and six ways of enhancing their waste management practices. Barriers include, among others, low environmental consciousness/awareness, lack of enforcement of environmental laws, and non-adherence to policies guiding solid waste management in the school. Ways of enhancing practices, include: provision of waste bins and containers at strategic places, etc. There was no significant difference between the male and the female undergraduate students and barriers to proper solid waste management practices (p > .05). It was recommended, among others, that the school management should provide more waste bins at strategic places.